Ion Conductivity and Transport by Porous Coordination Polymers and Metal–Organic Frameworks - Horike, Satoshi; Umeyama, Daiki; Kitagawa, Susumu (Accounts of chemical research, 2013)
Ion conduction and transport in solids are both interesting and useful and are found in widely distinct materials, from those in battery-related technologies to those in biological systems. Scientists have approached the synthesis of ion-conductive compounds in a variety of ways, in the areas of organic and inorganic chemistry. Recently, based on their ion-conducting behavior, porous coordination polymers (PCPs) and metal–organic frameworks (MOFs) have been recognized for their easy design and the dynamic behavior of the ionic components in the structures. These PCP/MOFs consist of metal ions (or clusters) and organic ligands structured via coordination bonds. They could have highly concentrated mobile ions with dynamic behavior, and their characteristics have inspired the design of a new class of ion conductors and transporters. In this Account, we describe the state-of-the-art of studies of ion conductivity by PCP/MOFs and nonporous coordination polymers (CPs) and offer future perspectives. PCP/MOF structures tend to have high hydrophilicity and guest-accessible voids, and scientists have reported many water-mediated proton (H+) conductivities. Chemical modification of organic ligands can change the hydrated H+ conductivity over a wide range. On the other hand, the designable structures also permit water-free (anhydrous) H+ conductivity. The incorporation of protic guests such as imidazole and 1,2,4-triazole into the microchannels of PCP/MOFs promotes the dynamic motion of guest molecules, resulting in high H+ conduction without water. Not only the host–guest systems, but the embedding of protic organic groups on CPs also results in inherent H+ conductivity. We have observed high H+ conductivities under anhydrous conditions and in the intermediate temperature region of organic and inorganic conductors. The keys to successful construction are highly mobile ionic species and appropriate intervals of ion-hopping sites in the structures. Lithium (Li+) and other ions can also be transported. If we can optimize the crystal structures, this could offer further improvements in terms of both conductivity and the working temperature range. Another useful characteristic of PCP/MOFs is their wide application to materials fabrication. We can easily prepare heterodomain crystal systems, such as core–shell or solid solution. Other anisotropic morphologies (thin film, nanocrystal, nanorod, etc.,) are also possible, with retention of the ion conductivity. The flexible nature also lets us design morphology-dependent ion-conduction behaviors that we cannot observe in the bulk state. We propose (1) multivalent ion and anion conductions with the aid of redox activity and defects in structures, (2) control of ion transport behavior by applying external stimuli, (3) anomalous conductivity at the hetero-solid–solid interface, and (4) unidirectional ion transport as in the ion channels in membrane proteins. In the future, scientists may use coordination polymers not only to achieve higher conductivity but also to control ion behavior, which will open new avenues in solid-state ionics.